2016
DOI: 10.3389/fnagi.2016.00168
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Results in Differential Gene Expression after Mild Traumatic Brain Injury and Is Linked to Imaging Differences at Acute Follow-up

Abstract: Older age consistently relates to a lesser ability to fully recover from a traumatic brain injury (TBI); however, there is limited data to explicate the nature of age-related risks. This study was undertaken to determine the relationship of age on gene-activity following a TBI, and how this biomarker relates to changes in neuroimaging findings. A young group (between the ages of 19 and 35 years), and an old group (between the ages of 60 and 89 years) were compared on global gene-activity within 48 h following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…The NF-κB pathway has been implicated in the regulation of proinflammatory cytokines during meningitis (51) and in bloodbrain barrier permeability (52). Moreover, the NF-κB pathway has been found to be dysregulated in clinical studies of acute and subacute TBI (7)(8)(9)(10). Upregulation of AKT1 in this sample suggests activation of the NF-κB pathway; a finding that supports these prior studies, although the specific role of AKT1 in blast effects on the central nervous system remains to be examined.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The NF-κB pathway has been implicated in the regulation of proinflammatory cytokines during meningitis (51) and in bloodbrain barrier permeability (52). Moreover, the NF-κB pathway has been found to be dysregulated in clinical studies of acute and subacute TBI (7)(8)(9)(10). Upregulation of AKT1 in this sample suggests activation of the NF-κB pathway; a finding that supports these prior studies, although the specific role of AKT1 in blast effects on the central nervous system remains to be examined.…”
Section: Discussionsupporting
confidence: 73%
“…Differential gene expression is reported in a small number of clinical TBI studies (7)(8)(9)(10), with few studies relevant to blast TBI (11)(12)(13). Gene expression regulation is imperative to appropriate cellular response to external mechanical, environmental, or biological stimuli, and the nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) complex is a main transcription factor of these adaptive gene expression changes (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR15 and LRRN3 have DNA methylation loci in their promoter regions that are reported to be hypomethylated among smokers which might indicate smoking‐induced epigenetic changes . LRRN3 is an inflammatory regulatory gene related to T‐cell function and immunosenescence whose expression declines with age and smoking, perhaps resulting in a dysregulated immune system prior to and after stroke. Claudin domain‐containing 1 (CLDND1), also known as claudin‐25, plays a role in the development of cerebrovascular disease in stroke‐prone spontaneously hypertensive rats .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TGF-β is up-regulated in brain tissue [61], while down-regulated in the serum of patients with AD [62]. NOG belongs to the transforming growth factor-β superfamily and is associated with neurorecovery and neuroregeneration [63]. Bonaguidi et al and Yousef et al found that NOG signaling changes with age and involved in the age-related neurological impairments and reductions in neuroregeneration [64,65].…”
mentioning
confidence: 99%